Quiet until the thaw : a novel - Fuller, Alexandra, 1969- (Penguin Press, 2017)
"From bestselling memoirist Alexandra Fuller, a debut novel. Lakota Oglala Sioux Nation, South Dakota. Two Native American cousins, Rick Overlooking Horse and You Choose Watson, though bound by blood and by land, find themselves at odds as they grapple with the implications of their shared heritage. When escalating anger towards the injustices, historical and current, inflicted upon the Lakota people by the federal government leads to tribal divisions and infighting, the cousins go in separate directions: Rick chooses the path of peace; You Choose, violence. Years pass, and as You Choose serves time in prison, Rick finds himself raising twin baby boys, orphaned at birth, in his meadow. As the twins mature from infants to young men, Rick immerses the boys within their ancestry, telling wonderful and terrible tales of how the whole world came to be, and affirming their place in the universe as the result of all who have come before and will come behind. But when You Choose returns to the reservation after three decades behind bars, his anger manifests, forever disrupting the lives of Rick and the boys. A complex tale that spans generations and geography, Quiet Until the Thaw conjures with the implications of an oppressed history, how we are bound not just to immediate family but to all who have come before and will come after us, and, most of all, to the notion that everything was always, and is always, connected. As Fuller writes, "The belief that we can be done with our past is a myth. The past is nudging at us constantly.""--